(untitled) (Revista Logos Ciencia & Tecnología, 2022)
This article reports an action research study to solve the problem that twenty-two English language students from a school in Cartagena de Indias considered that the current teaching was inadequate and that they needed to develop topics of interest, aural-oral skills and acquire vocabulary. The authors adjusted their practices, combined global and local themes, and brought multimodal texts to respond to the problem. The action stage of the study required the structuring of the course with themes of the identity of Cartagena de Indias under a Task-Based Learning methodology. The use of information and communication technologies was forced by the challenge of Covid19, which demanded an abrupt transition from face-to-face to remote teaching and thus the inclusion of computer literacy. The new syllabus included topics close to the identity of the participants such as historical landmarks, economy, and tourism to simulate being a Cartagena tour guide so that learning was contextualized, evocative and expressive. The article presents one of the six workshops followed by an analysis of the data collected. The results of the study show that there were gains in language development attributable to the theme of global-local issues in the workshops that took half a school year. The pedagogical innovation also gave positive results in verbal fluency in which technological mediations and Task-Based Learning played an important role.